Interdisciplinary Linguistic and Psychiatric Research on Language Disorders 2019
DOI: 10.17234/9789531758314.06
|View full text |Cite
|
Sign up to set email alerts
|

Shared lexical-semantic features and the animacy effect in early-course psychosis

Abstract: Language deficits in psychosis, and in schizophrenia, are presumed to be due to increased activation and connectivity of the semantic memory, which is determined by lexical-semantic features of concepts. The aim of this study was to analyse the influence of shared lexical-semantic features on language processing in patients with first-episode and early-course psychosis. The study included 15 Croatian-speaking patients from the University Psychiatric Hospital Vrapče, Zagreb, diagnosed with first-episode and ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Neuroscientific research has clearly demonstrated that semantic memory is widely distributed over the cortical surface and the processing of different semantic categories may be associated with disproportionate levels of metabolic activity in different brain regions (Gainotti, 2015;Huth et al, 2016). Furthermore, both theoretical and experimental linguistics agree that different lexical-semantic features such as concreteness/abstractness and animacy/inanimacy underlie divergent cognitive processing mechanisms, while pathological populations may exhibit featurespecific deficits on lexical tasks (Carammaza & Shelton, 1998;Sekulić Sović et al, 2019).…”
Section: Category-specific and Letter-specific Effects On Verbal Fluency Performancementioning
confidence: 99%
“…Neuroscientific research has clearly demonstrated that semantic memory is widely distributed over the cortical surface and the processing of different semantic categories may be associated with disproportionate levels of metabolic activity in different brain regions (Gainotti, 2015;Huth et al, 2016). Furthermore, both theoretical and experimental linguistics agree that different lexical-semantic features such as concreteness/abstractness and animacy/inanimacy underlie divergent cognitive processing mechanisms, while pathological populations may exhibit featurespecific deficits on lexical tasks (Carammaza & Shelton, 1998;Sekulić Sović et al, 2019).…”
Section: Category-specific and Letter-specific Effects On Verbal Fluency Performancementioning
confidence: 99%
“…However, neuroscientific research has clearly demonstrated that semantic memory is widely distributed over the cortical surface and different semantic categories may be associated with disproportionate levels of metabolic activity in different brain regions (Huth et al 2016). Furthermore, both theoretical and experimental linguistics agree that different lexical-semantic features such as concreteness/abstractness and animacy/inanimacy underlie divergent cognitive processing mechanisms (Ventura et al 2005), while pathological populations may exhibit feature-specific deficits on lexical tasks (Carammaza & Shelton 1998;Sekulić Sović et al 2019). Similarly, processing of different phonological categories is associated with different cognitive and neural mechanisms (Lago et al 2015).…”
Section: Category-specific and Letter-specific Effects On Verbal Fluency Performancementioning
confidence: 99%